BIO-PHYSICAL AND SOCIO-ECONOMIC EFFECTS OF QUARRYING ACTIVITIES IN SELECTED QUARRIES IN TEZO WARD-KILIFI COUNTY - Wambua, Agnes; Chege, James; Ngira, Amos (International Journal of Environmental Sciences, 2021)
Purpose: Using a Systems' Approach, this study explores what aspects are essential for stone quarries to adopt a functional environmental management plan and whether compliance with environmental laws enhances business performance. The specific objectives of the study were: To evaluate the bio-physical effects of quarrying activities in selected quarries in Tezo ward and to evaluate the socio-economic effects of quarrying activities in selected quarries in Tezo ward. Methodology: The study adopted descriptive survey design; the research data collection instrument was questionnaires. The study adopted purposive sampling; a survey of 134 respondents representing 80 quarry workers, 40 quarry owners, 10 EIA Experts, 3 NEMA staff and 1 County geologist were sampled purposively. Weighted and the Consolidated Scores were entered on Microsoft Excel for cleaning and later transferred to Statistical Package for Social Sciences (SPSS version 23.0) for statistical analyses. Data was presented inform of graphs, pie-charts, tables and narration in the thematic areas. Findings: The study found out that there were health and ecological problems associated with quarrying. The application of heavy quarrying machines resulted to soil erosion, destruction of flora and threatens biodiversity aesthetic. The study revealed that quarrying was a source for livelihood among the community and more men (90%) were involved in quarrying due to masculinity nature of the task. EMPs were found to be significant in management of quarries. The development of EMPs and EIA was influenced by different actors and informal sector was a significant influencer of EMPs implementation. The study concluded that EMPs were effective in management of quarries despite varied challenges facing the NEMA official and the EIA experts. Unique contribution to theory, practice and policy: The study recommends the need for transparency in the EIA as well as in the development of EMPs, to avoid discrimination and non-adherence. Further research is needed to understand the perception of community members on the effectiveness of EMPs in sustainable management of quarries and environment in general.